ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), NON PERFORMING LOAN (NPL), NET INTEREST MARGIN (NIM) DAN BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSET (ROA) PADA BADAN USAHA MILIK NEGARA (BUMN) T - Ababiel, Firdaus Ananta; Nasution, R. (Peneliti.net, 2024)
The purpose of this study was to determine and test the effect of the Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loans, Net Interest Margin and Operational Costs and Operating Income on Financial Performance, namely Return On Assets partially or simultaneously. This study uses secondary data with the 2013-2022 research period. The data used comes from the banking annual financial reports which have been published from each bank's website and have been registered on the Indonesia Stock Exchange (IDX) for the 2012-2021 period. The method used is multiple linear analysis to identify the complex relationship between the independent and dependent variables. The data used comes from a purposive sampling technique, which is carried out based on certain characteristics of these banks. Data is processed using SPSS 16. The results of the study used statistical tests that the effect of Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loans, Net Interest Margin and Operating Costs and Operating Income on Financial Performance, namely Return On Assets simultaneously had an effect. However, partially the Capital Adequacy Ratio has a significant negative effect on Return On Assets. Loan to Deposit Ratio has no effect on Return On Assets. Non Performing Loans have no effect on Return On Assets. Net Interest Margin has a partially significant positive effect on Return On Assets and Operational Costs and Operating Income has a partially significant negative effect on Return On Assets at BUMN Banks listed on the Indonesia Stock Exchange in 2013-2022. This research provides an in-depth understanding of the factors that influence the financial performance of state-owned banks in Indonesia. These findings can serve as a guide for bank management and regulatory authorities in designing more effective strategies to increase the profitability and operational efficiency of these banks.